Chlorine gas poisoning by trichloroisocyanuric acid and respiratory failure: a case report of a 49-year-old patient - Wang, Yamei; Meng, Jun; Tian, Xiaowei; Sun, Chuihua; Liu, Lu; Sun, Xiaojuan (Frontiers in Medicine, 2025)
BackgroundTrichloroisocyanuric acid (TCCA) is a potent disinfectant and bleaching agent widely used in industrial applications. When TCCA comes into contact with water, chlorine gas and hypochlorous acid are produced. Although acute respiratory distress syndrome (ARDS) induced by chlorine gas inhalation is rare, if untreated, it can progress to severe respiratory failure. Currently, no standardized glucocorticoid dosing protocol exists for ARDS management in such cases.Case presentationThis report details the case of a 49-year-old male who developed ARDS following chlorine gas inhalation during an occupational TCCA incident. Upon admission, the patient exhibited shortness of breath, coughing, and dyspnea. Initial laboratory tests revealed leukocytosis and elevated inflammatory markers. Imaging showed bilateral patchy ground-glass opacities, and arterial blood gas analysis indicated severe hypoxia. The patient was treated with non-invasive mechanical ventilation and a graded corticosteroid regimen, leading to gradual improvement in his clinical condition. During this course, the patient developed fever, frequent dry cough, and occasional sputum production. Sputum cultures identified Candida albicans as the pathogen, prompting a shift in treatment to include fluconazole for antifungal therapy, cefoperazone-sulbactam for antibacterial coverage, and continued corticosteroid therapy. The patient recovered progressively and was discharged on the 51st day without complications.ConclusionChlorine gas inhalation can result in severe ARDS, underscoring the need for early diagnosis and prompt intervention. This case underscores the importance of a graded corticosteroid regimen in combination with non-invasive mechanical ventilation in ARDS management. Additionally, fluconazole and cefoperazone effectively address secondary pulmonary fungal infections caused by Candida albicans.